COMPARATIVE STUDY OF OPEN-LOOP AND CLOSED-LOOP IDENTIFICATION OF MIMO SYSTEMS - MOHD SHAH, MOHAMED IMRAN SHAH (IRC, 2017)
This paper consists of Comparative Study of Open-loop and Closed-loop Identification of Multiple-Input Multiple-Output (MIMO) Systems. The work is employing System Identification approach. The aim of this research is to compare the accuracy of Open-loop and Closed-loop Identification developed using the data extracted from Continuous Stirred Tank Reactor (CSTR) reactor model. The Controller used for Closed-Loop System is PID Controller. The model structure used in every model is either ARX model and ARMAX model. To improve dynamic characteristic of the output, Pseudo Random Binary Sequence (PRBS) and White noise was introduced into the system. Each dataset consists of 3000 sample, but separated into main estimation data and validation data the for model with ratio of 2000:1000, respectively. All the analysis work is done via MATLAB R2015a Software. The result generated indicates that Closed-Loop system give better accuracy compared to Open-Loop system and ARMAX model structure yield a better accuracy when compared to ARX model structure. However, generally both models ARX and ARMAX model structures can be implemented since it passes all the validation's criteria in this study; model fits, correlation test and distribution of the residual. This finding is important and it will benefits for further work in controller design and real time application.